Mpox, HIV infection, and genital skin disease: triple burden, threats and challenges from an epidemiological perspective - Adnyana, I Made Dwi Mertha; Eljatin, Dwinka Syafira; Maulana, Sidik; Ibrahim, Kusman; Umar, Tungki Pratama; Armini, Luh Nik; Cruz, Zito Viegas da (PT. Mega Science Indonesia, 2024)
The expansion and transformation of Mpox (MPX) disease alongside HIV and genital skin diseases has led to an increase in global morbidity and mortality in a relatively brief period. These diseases have a similar transmission pathway through sexual intercourse (mainly MSM/men-sex with males). This review aims to provide a concise, evidence-based overview of MPX, HIV, and genital skin disease coinfections, and to identify epidemiological threats and challenges. Our investigations revealed that from January 2022 to July 2023, there was a significant increase in the number of MPX cases, which reached a total of 88,600, resulting in 152 deaths across 113 countries. There have been case reports of triple-burden disease in six different areas of the world, with at least 52% of reported cases occurring in men who have had sexual activity with other men, 84.1% of whom do not use condoms and do not take pre-exposure prophylaxis (PrEP). In addition, the highest number of deaths due to co-infection with MPX, HIV infection, and genital skin diseases occurred in vulnerable groups (LGBTQIA2S+), especially in men who had sex with men, up to 90.9%, and experienced an increase in the frequency of triple burden diseases to 104.9%. From an epidemiological standpoint, this condition generates several threats and challenges, including an increasing burden of infectious diseases, an increase in immunocompromised populations, an increase in overlapping risk factors, diagnostic difficulties, an increase in interactions and comorbidities, and relatively complex treatment challenges. To suppress these outbreaks and pandemics, comprehensive control and prevention should be proposed collaboratively, including collaboration with the education sector to conduct better research and investigation using one health in complex settings. Epidemiological modeling can be used in the future to accelerate the control of these diseases.